Lutte contre Pseudomonas aeruginosa responsable des infections nosocomiales - ACHACHE, Hadjer; BOUKOUCHA, Nadjet (My University, 2025)
Nosocomial infections represent a major public health issue, particularly due to the increasing antibiotic resistance of Pseudomonas aeruginosa. This study focused on evaluating the antimicrobial activity of several natural extracts, including plant extracts (Lawsonia inermis, Allium sativum), 13 fungal isolates (one identified as Aspergillus sp.), and honey, against two P. aeruginosa strains : a reference strain (ATCC 27853) and a clinical isolate (I1). The results revealed that only the extracts of A. sativum, L. inermis, and Aspergillus sp. exhibited significant antimicrobial activity. For Aspergillus sp., inhibition zones measured 20,6 mm (ATCC strain) and 20 mm (I1 Isolate), with a MIC of 25 mg/mL and an MBC of 50 mg/ml. A. sativum showed inhibition zones of 22,1 mm (ATCC strain) and 9,8 mm (I1 Isolate), with MIC and MBC values of 25% and 50%, respectively. L. inermis showed inhibition zones of 13,3 mm (ATCC strain) and 12,4 mm (I1 Isolate), with both MIC and MBC values of 7,5 mg/ml. A CMB/MIC ratio of 1 was observed for A. sativum and L. inermis, indicating marked bactericidal activity. Moreover, co-culture with Aspergillus sp. led to an increase in pyocyanin production in the ATCC strain (from 1,758 to 2,527 μg/ml), while a slight decrease was observed in the I1 isolate (from 0,734 to 0,666 μg/ml). These results suggest a strong potential for these natural extracts as therapeutic alternatives against multidrug-resistant P. aeruginosa strains and justify further research for in vivo and clinical applications.
Keywords: Pseudomonas aeruginosa, nosocomial infections, antibiotic resistance, Allium sativum, Lawsonia inermis, Aspergillus sp., antibacterial activity, pyocyanin